Intermittent versus Continuous Catheterization and Differences in the Evolution of Labor: Systematic Review and Meta-analysis - Inês Reis; Sara Cunha; Matilde Martins; Luísa Sousa; Adérito Seixas; Cátia Rasteiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To evaluate the differences between bladder emptying options (permanent catheterization and intermittent bladder emptying/spontaneous urination) regarding the effects on labor length, need of operative vaginal deliveries, and cesarean section rate. Data Sources The search was conducted in MEDLINE, Scopus, Web of Science, and The Cochrane Central Register of Controlled Trials databases. Selection of Studies The survey returned 964 studies. A total of 719 studies were evaluated by title and abstract, of which 4 were selected for inclusion. Data Collection All references were inserted in the Rayyan QCRI tool (Rayyan Systems Inc., Cambridge, MA, USA). The full text of the selected articles was obtained so we could later decide whether or not to include them in this systematic review. Data Synthesis No differences were found in the number of instrumented deliveries or in cesarean section rate between groups. Conclusions After evaluating the studies performed on the topic, we concluded that there is no clear advantage to either method, although continuous catheterization was associated with a greater occurrence of eutocic births. In the remaining outcomes, there were no differences between catheterization types.